Renal palliative and supportive care in South Africa – a consensus statement - Wearne, Nicola; Krause, Rene; Davidson, Bianca; Brennan, Frank (African Journal of Nephrology, 2020)
In South Africa, there is a high burden of end-stage kidney disease (ESKD). This is due to the burgeoning epidemics of communicable diseases like HIV/AIDS and non-communicable diseases, particularly hypertension and diabetes mellitus. One of the most difficult situations encountered by healthcare professionals dealing with patients with ESKD in South Africa is the management of a conservative or palliative care pathway for the many patients who have no other option. Patients with advanced chronic kidney disease (CKD) have a high burden of physical and psychosocial symptoms, poor outcomes, and high costs of care. Many patients are managed in primary healthcare settings and either do not have access to palliative care or are not referred appropriately. Renal supportive and palliative care involves a multidisciplinary approach to managing patients with ESKD, to ensure that symptoms are managed optimally and to provide support during advanced disease. It aims to improve quality of life for patients and their families and must be provided alongside curative medical care. This support should include those unable to gain access to life-saving dialysis and it should also provide care for patients where dialysis is not the best option. The aim of this consensus statement is to assist healthcare providers to improve the management of symptoms and biosocial factors of patients with end-stage kidney disease in a South African context. The document was compiled through consensus building among healthcare professionals across South Africa. The professionals that are represented included nephrologists, palliative care physicians, social workers, nurses, paediatricians and hospital managers. We wish to acknowledge the contribution of Dr Frank Brennan, a leading expert in renal palliative and supportive care, who assisted greatly in the compilation of this document.